ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI OUTSTANDING KREDIT UMUM PEDESAAAN (KUPEDES) PT BANK RAKYAT INDONESIA (PERSERO), TBK - Erric Wijaya; Kesuma wardhani (Media Ekonomi, 2010)
Most businesses in Indonesia are Micro, Small, and Medium Enterprises (MSME). MSMEhave a significant role on the economy. In banking sector, the credit financing in MSMEgives many benefits. This evidence pushes the demand of micro banking market. Fromthe moment it’s established, BRI who has a business focus in MSME through creditfinancing program which is Kupedes, should know the important factor that have to bemaintain to keep the growth of its credit finance. This research uses a multiple linearregression analysis to determine the influence of independent variables on dependentvariable. Independent variables in this research represented by Kupedes interest rate,Gross Domestic Product (GDP), number of BRI Units, and Kredit Usaha Rakyat (KUR)Program, while the dependent variable is reflected by outstanding Kupedes. The results ofthis study indicates that Kupedes interest rate, Gross Domestic Product (GDP), number ofBRI Units, and KUR program have significant influence on outstanding Kupedessimultaneously. In addition, Kupedes interest rate, GDP, and number of BRI Units alsohave significant influence on outstanding Kupedes partially, while KUR program has nosignificant influence on outstanding Kupedes partially.